STRENGTHENING NATIONAL CULTURE IN SCHOOLCHILDREN THROUGH VISUAL ARTS: PRACTICAL RECOMMENDATIONS - Usmonova Ruxshona Feruz qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores practical strategies for strengthening schoolchildren’s understanding and appreciation of national culture through visual arts lessons. The study emphasizes methods that combine creative activities, cultural motifs, and artistic techniques to enhance students’ cultural awareness, aesthetic perception, and creative expression. By integrating hands-on exercises, interactive tasks, and project-based learning, teachers can foster students’ connection to their national heritage while developing artistic skills. The article provides practical recommendations for designing and implementing visual arts lessons that promote both cultural knowledge and creativity.